2010
DOI: 10.1524/ract.2010.1739
|View full text |Cite
|
Sign up to set email alerts
|

Application of indigenous inorganic sorbents in combination with membrane technology for treatment of radioactive liquid waste from decontamination processes

Abstract: Zeolites / Decontamination / Radioactive waste microfiltration / UltrafiltrationSummary. The purpose of the work was to improve the process for treatment of liquid radioactive waste containing complexing agents, which are generated during the decontamination operations.We performed some experiments using simulated waste solutions like secondary waste from the modified CANDEREM process (Canadian Decontamination and Remediation Process) and secondary waste from the modified CANDECON process (Canadian Decontamina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The decontamination efficiency achieves 99.94% and the volume concentration ratio achieves 12.5 at pH 10 for solution fed into the membrane separation system. Dulama et al (2010) proposed to treat the waste by combining the sorption of radionuclides on natural inorganic sorbents (zeolites) with membrane filtration. Zhu et al (2014a, b) prepared PVA/chitosan magnetic composite beads and used for Co 2+ removed from radioactive waste.…”
Section: +mentioning
confidence: 99%
“…The decontamination efficiency achieves 99.94% and the volume concentration ratio achieves 12.5 at pH 10 for solution fed into the membrane separation system. Dulama et al (2010) proposed to treat the waste by combining the sorption of radionuclides on natural inorganic sorbents (zeolites) with membrane filtration. Zhu et al (2014a, b) prepared PVA/chitosan magnetic composite beads and used for Co 2+ removed from radioactive waste.…”
Section: +mentioning
confidence: 99%
“…The performance of different sorbents was compared by determining the ion exchange capacity, distribution coefficients, and evaluating the sorption characteristics. The obtained results showed that the distribution coefficients of Cs on the Na-form converted materials are higher than for that of NH 4 -and H-forms [41,42]. The biosorption of U by seaweed Sargassum filipendula was investigated under dynamic conditions at various bed heights [43].…”
Section: Miscellaneous Methodsmentioning
confidence: 99%
“…4 Numerous studies have shown 6 that U(VI) is present in environmental water and wastewater mainly in the soluble anionic carbonate forms such as UO 2 (CO 3 ) 2 2− and UO 2 (CO 3 ) 3 4− which are not sufficiently eliminated by mineral suspensions and clay components of soils. Numerous methods have been proposed to remove U(VI) from waste and contaminated environmental water 7 such as solvent extraction, 8 distillation, 9 coagulation, 10 reverse osmosis, 11 precipitation, 12 adsorption/ion exchange, 13 membrane ltration and biological technologies. 14 Each of these methods has its advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous methods have been proposed to remove U( vi ) from waste and contaminated environmental water 7 such as solvent extraction, 8 distillation, 9 coagulation, 10 reverse osmosis, 11 precipitation, 12 adsorption/ion exchange, 13 membrane filtration and biological technologies. 14 Each of these methods has its advantages and disadvantages.…”
Section: Introductionmentioning
confidence: 99%